The purity of impure public goods - Anja Brumme; Wolfgang Buchholz; Dirk Rübbelke (Journal of Public Economic Theory, 2022)
In this paper, we provide a new perspective on the links between the analysis of the voluntary provision of pure and impure public goods. In particular, it is shown that the impure public good model can be transformed into a pure public good one. This innovative method not only leads to new comparative statics results, but also provides new insights on the impure public good model, for example, on causes of the nonneutrality of income transfers with regard to Nash equilibria in the impure public good case.
Keywords: 330